If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + (3y + 1) + 20 + (3y + 1) = 0 Reorder the terms: 20 + (1 + 3y) + 20 + (3y + 1) = 0 Remove parenthesis around (1 + 3y) 20 + 1 + 3y + 20 + (3y + 1) = 0 Reorder the terms: 20 + 1 + 3y + 20 + (1 + 3y) = 0 Remove parenthesis around (1 + 3y) 20 + 1 + 3y + 20 + 1 + 3y = 0 Reorder the terms: 20 + 1 + 20 + 1 + 3y + 3y = 0 Combine like terms: 20 + 1 = 21 21 + 20 + 1 + 3y + 3y = 0 Combine like terms: 21 + 20 = 41 41 + 1 + 3y + 3y = 0 Combine like terms: 41 + 1 = 42 42 + 3y + 3y = 0 Combine like terms: 3y + 3y = 6y 42 + 6y = 0 Solving 42 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 6y = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 6y = 0 + -42 6y = 0 + -42 Combine like terms: 0 + -42 = -42 6y = -42 Divide each side by '6'. y = -7 Simplifying y = -7
| y=7*6+2 | | 2x-3y+14=0 | | 5n+4=14-6 | | 4x+23=10x-19 | | y=ln(sqrt(x^2+-1)) | | 3x4/5x1/8 | | 2m+5n=2 | | 10x+5=25-5 | | 2x^2+4=2x+6 | | 2x-3=5+3x | | (5/6)=((w-2)/4) | | m-10n=6 | | 5(x-2)=16 | | 1=x+0.56x | | 37=5w-13 | | p(x)=2x^2+5x+1 | | 3x^2+26x=16 | | 5x+43=8x-19 | | 12z+28-7z-3= | | 6x+1=34-5x | | 32+(x-2)+32+(x-2)= | | 1.95y+6.834=7.65y-19.8591 | | 70=-7 | | 3*(x-31)=x-13 | | 5-4(6-3)= | | 13x-32=9x-4 | | 182=7(-5v-9) | | 7+8(3-9)= | | 13x+15=11x-2 | | (-3i)(8i)= | | 6-6x(9-9)/1/(2x6) | | 31/7=93/t |